Proprioceptive Precision and Degree of Visuo-Proprioceptive Discrepancy Do Not Influence the Strength of the Rubber Hand Illusion. (September 2019) - Motyka, Paweł; Litwin, Piotr
Rubber hand illusion is caused by spatiotemporally congruent visuotactile stimulation which induces a sense of ownership towards a fake limb. We tested two predictions of the Bayesian bottom-up model; namely, that the strength of the illusion is inversely proportional to (a) the distance separating hands and (b) the precision of proprioceptive signals. To manipulate distance, we displaced participants' hands to either a position close to (8 cm) or far from (24 cm) the rubber hand. Before manipulation, we assessed proprioceptive abilities in a task requiring active reproduction of one's arm's position. Proprioceptive precision was operationalised as inversely related to the variance of the estimations. Multiple regression showed that both for subjective and physiological measures neither distance, nor proprioceptive precision, nor their interaction were predictors of illusion strength. Bayes factor analyses provided evidence for null effects. Our findings suggest the limited relevance of proprioception for the strength of visuo-haptically induced rubber hand illusion.